2009
DOI: 10.1177/0192623308329286
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Acute-phase Proteins as Inflammatory Biomarkers in Preclinical Toxicology Studies: Implications for Preclinical to Clinical Translation

Abstract: Recently, in early clinical development, a few biologics and small molecules intended as antitumor or anti-inflammatory agents have caused a severe adverse pro-inflammatory systemic reaction also known as systemic inflammatory response syndrome (SIRS). This toxicity could result from expected pharmacological effects of a therapeutic antibody and/or from interaction with antigens expressed on cells/tissues other than the intended target. Clinical monitoring of SIRS is challenging because of the narrow diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Elevated CRP and fibrinogen are consistent with activating the IL22 pathway in liver hepatocytes, and elevated REG3A is consistent with activating the IL22 pathway in intestinal and pancreatic acinar epithelial cells . In contrast to the cynomolgus monkeys, rats did not exhibit increases in CRP and fibrinogen levels as rats utilize a different acute‐phase response than monkeys . Results from the monkey studies demonstrated that serum REG3A levels were increased, and correlated with UTTR1147A drug levels.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Elevated CRP and fibrinogen are consistent with activating the IL22 pathway in liver hepatocytes, and elevated REG3A is consistent with activating the IL22 pathway in intestinal and pancreatic acinar epithelial cells . In contrast to the cynomolgus monkeys, rats did not exhibit increases in CRP and fibrinogen levels as rats utilize a different acute‐phase response than monkeys . Results from the monkey studies demonstrated that serum REG3A levels were increased, and correlated with UTTR1147A drug levels.…”
Section: Discussionmentioning
confidence: 73%
“…5,25,26 In contrast to the cynomolgus monkeys, rats did not exhibit increases in CRP and fibrinogen levels as rats utilize a different acute-phase response than monkeys. 23 REG3A, partially protected against weight loss and mortality in IL22−null mice infected with Citrobacter rodentium. 5 As with the skin findings, these transient dose-dependent elevations in acutephase proteins as well as in REG3A were observed in human clinical trials.…”
Section: Discussionmentioning
confidence: 95%
“…50 ATF6 has been linked to acute-phase-response, a broad immunological process associated with infiltration and activation of inflammatory cells and production of inflammatory mediators. 51 Cleavage of ATF6 leads to transcriptional activation of a set of acute-phase proteins such as C-reactive protein (CRP), which is a well-known marker of systemic inflammatory response. CRP can cause elevated expression of MCP-1 receptor and thus contribute to inflammation.…”
Section: Er Stress In Inflammationmentioning
confidence: 99%
“…Nothing can be done to change the molecular properties of the drug at that time. On the other hand, animal results do not always translate to humans accurately, due to several factors, including species differences and genetic variability 84. Contemporary in silico approaches to ADR prediction concentrate on docking studies and Structure–Activity Relationship (SAR)/QSAR models for the identification of structural features with ADR propensity 85,86.…”
Section: Discussionmentioning
confidence: 99%